The Effect of Osteoporotic Vertebral Fracture on Quality of Life - Merih Eryavuz Sarıdoğan; Ülkü Akarırmak; Bahar Çakmak; Günay Can (Galenos Yayinevi, 2002)
Aim: The aim of this study was to evaluate the effect of vertebral fracture on life quality by two different measures. Methods: This clinical study was performed in the Osteoporosis Clinic of our PTR Departmant and comprised of 25 female patients with osteoporotic vertebral fracture on x-ray and 12 control patients. Inclusion Criteria: 55-80 year age group , at least five years of menopause, one or several vertebral fractures. Exclusion Criteria: New vertebral fracture (less than one month), new femoral fracture, secondary osteoporosis . Control group consisted of persons in the same age group, without osteoporosis or cronic back and low back pain. Results: Assessment by QUALEFFO-41 revealed no significant difference between patient and control group concerning pain, activites of daily living and free time activities. Significant difference for pain caused by walking, climbing stairs and raising from a chair, general health and mental function were found (p=0.05). Assessment by SF-36 showed significant difference between the two groups for climbing stairs, bending and kneeling as well as general mental health and awareness of general health status (p=0.05). Conclusion: QUALEFFO-41 and SF-36 both are tools which can be used for assessment of quality of life in women with osteoporotic vertebral fracture.